Evaluation of plasma biomarkers of inflammation in patients with maple syrup urine disease. Issue 4 (8th May 2018) - Scaini, Giselli; Tonon, Tássia; Moura de Souza, Carolina F.; Schuck, Patricia F.; Ferreira, Gustavo C.; Quevedo, João; Neto, João Seda; Amorim, Tatiana; Camelo, Jose S.; Margutti, Ana Vitoria Barban; Hencke Tresbach, Rafael; Sperb‐Ludwig, Fernanda; et al.
Abstract: Maple syrup urine disease (MSUD) is an autosomal recessive inherited disorder that affects branched‐chain amino acid (BCAA) catabolism and is associated with acute and chronic brain dysfunction. Recent studies have shown that inflammation may be involved in the neuropathology of MSUD. However, these studies have mainly focused on single or small subsets of proteins or molecules. Here we performed a case‐control study, including 12 treated‐MSUD patients, in order to investigate the plasmatic biomarkers of inflammation, to help to establish a possible relationship between these biomarkers and the disease. Our results showed that MSUD patients in treatment with restricted protein diets have high levels of pro‐inflammatory cytokines [IFN‐γ, TNF‐α, IL‐1β and IL‐6] and cell adhesion molecules [sICAM‐1 and sVCAM‐1] compared to the control group. However, no significant alterations were found in the levels of IL‐2, IL‐4, IL‐5, IL‐7, IL‐8, and IL‐10 between healthy controls and MSUD patients. Moreover, we found a positive correlation between number of metabolic crisis and IL‐1β levels and sICAM‐1 in MSUD patients. In conclusion, our findings in plasma of patients with MSUD suggest that inflammation may play an important role in the pathogenesis of MSUD, although this process is not directly associated with BCAA blood levels. Overall, data reported here are consistent with the working hypothesis that inflammation may be involved in the pathophysiological mechanism underlying the brain damage observed in MSUD patients.